Media Strategy and Place Branding in the Transnational European Öresund Region / Estrategia de medios y place branding en la region transnacional europea de Öresund - Jasper Falkheimer (Revista Internacional de Relaciones Públicas, 2014)
Purpose: The aim is firstly to to present a conceptual discussion about the relationship between media strategies and place branding, media effects and relations between sources and journalists. Second, based on a case study of the European transnational Öresund region (Danish-Swedish) the aim is to describe and analyze a contemporary agenda-building, media service-oriented place branding strategy.